A composite material of graphene-modified carbon nanotubes and preparation method thereof

Through the preparation method of modified carbon nanotubes, the problem of uneven oxidation and dispersion of carbon nanotubes in graphene composite materials is solved, efficient conductive network and electrochemical performance are achieved, and the thermal stability and application performance of the material are improved.

CN119390064BActive Publication Date: 2025-04-29ANHUI BONDRUI NEW MATERIAL TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411641715.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-04-29
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

During the preparation process of existing graphene/carbon nanotube composites, carbon nanotubes are susceptible to oxidation, destroying their integrity, resulting in a decrease in conductivity and uneven dispersion, affecting application performance.

Method used

The preparation method of modified carbon nanotubes, including carboxylation, acid chloride and reaction with 2-(4-aminophenyl)butyric acid, modify the surface of the carbon nanotube, improve its dispersion, and crosslink with modified graphene and metal ions to form an efficient conductive network.

Benefits of technology

The dispersion and conductivity of carbon nanotubes are improved, the separation between graphene layers is enhanced, agglomeration and stacking are avoided, specific capacitance and conductivity are improved, and efficient electrochemical performance and thermal stability are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390064B_ABST
    Figure CN119390064B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of graphene materials, and in particular to a composite material of graphene-modified carbon nanotubes and a preparation method thereof. The composite material tube cross-links the modified carbon nanotubes with graphene and metal ions to improve electrical properties. The composite material prepared by the present invention presents a surface-line network structure, and the nanotubes are uniformly dispersed between graphene sheets, having a large effective specific surface area, being conducive to the transmission of charges, and having excellent electrochemical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of graphene materials, and in particular to a composite material of graphene-modified carbon nanotubes and a preparation method thereof. Background Art

[0002] Graphene has good electrical conductivity and thermal conductivity, and has a large specific surface area, excellent mechanical properties, and good chemical stability. It can be used as a conductive additive in lithium-ion batteries to improve the electrical conductivity of electrode materials; it can also be used as a functional additive in composite materials to improve the electrical conductivity, thermal conductivity and mechanical properties of composite materials. It is widely used. However, due to its special two-dimensional structure, graphene is easy to agglomerate in practical applications, resulting in uneven dispersion, which limits its application performance. Carbon nanotubes, as one-dimensional nanomaterials, can be used as supports between graphene sheets, blocking the aggregation between graphene sheets, and achieving coordination between one-dimensional and two-dimensional carbon materials. At present, there are related literature reports on methods for preparing graphene / carbon nanotube composites, but the preparation methods in the related literature are all to use a simple mechanical mixing method to achieve compounding of graphene and carbon nanotubes (such as directly mixing and stirring graphene and carbon nanotubes), and both have the disadvantage of uneven dispersion of graphene and carbon nanotubes. In this regard, there are related invention patents that introduce a method of adding carbon nanotubes to the preparation process of graphene to prepare a graphene / carbon nanotube composite material, such as Chinese invention patent CN106861617B and Chinese patent application CN109994733A, both of which add carbon nanotube powder to the oxidation process of graphite to finally obtain a graphene / carbon nanotube composite material. Although the graphene / carbon nanotube composite material prepared by this method has better dispersion uniformity than the composite material prepared by direct mechanical mixing, the carbon nanotubes will also be oxidized to a certain extent during the graphite oxidation process, which destroys the integrity of the carbon nanotubes and reduces the conductivity of the carbon nanotubes. Summary of the invention

[0003] In view of the deficiencies in the prior art, the present invention provides a composite material of graphene-modified carbon nanotubes and a preparation method thereof.

[0004] The present invention is achieved through the following technical solutions:

[0005] A method for preparing a composite material of graphene-modified carbon nanotubes comprises the following steps:

[0006] S1: Preparation of modified carbon nanotubes:

[0007] S11: Preparation of 65wt% HNO 3 aqueous solution and 45wt% H 2 O 2 aqueous solution, HNO 3 Aqueous solution with H2 O 2 The aqueous solution is mixed to obtain HNO 3 / H 2 O 2 Mix the solution and add carbon nanotubes to HNO 3 / H 2 O 2 The mixed solution was stirred at 200-300 rpm for 30 min, ultrasonicated at 40-50 kHz for 30 min, heated under reflux at 120°C for 2 h, filtered, the filter cake was washed with deionized water, and vacuum dried at 80°C for 12 h to obtain carboxyl carbon nanotubes;

[0008] S12: adding thionyl chloride to the carboxyl carbon nanotubes obtained in step S11, ultrasonicating at 40 kHz for 20-30 min, stirring at 60-80°C and 200-300 rpm for 24-28 h, cooling to room temperature, filtering, washing with DMF and tetrahydrofuran, and vacuum drying at 80-100°C to obtain acyl chloride carbon nanotubes;

[0009] S13: the acyl chloride carbon nanotubes obtained in step S12 are fully mixed with 2-(4-aminophenyl)butyric acid, pyridine and DMF, and ultrasonicated at 40 kHz for 20-30 min, and nitrogen is passed for 20-25 min, and then stirred and refluxed at 110-130° C. and 500-600 rpm for 44-48 h, and vacuum filtered. The filter cake is washed with DMF and acetone, and dried at 80° C. to obtain modified carbon nanotubes;

[0010] S2: Preparation of modified graphene:

[0011] S21: Add dimethyl sulfoxide to benzimidazole, stir at 80-90°C and 150-200 rpm for 20 min, add 2,3-epoxypropyltrimethylammonium chloride, continue stirring and reacting at 80-90°C for 22-24 h, pour into acetone for precipitation, filter, wash with deionized water, and dry under vacuum at room temperature for 48 h to obtain imidazole quaternary ammonium salt;

[0012] S22: dispersing graphene oxide in deionized water, ultrasonicating at 600 W for 20-30 min, adding NaOH and chloroacetic acid, and continuing ultrasonicating for 2-3 h, centrifuging at 8000 rpm for 15-25 min, and vacuum drying at 60-70 °C to obtain carboxylated graphene;

[0013] S23: Take the carboxylated graphene obtained in step S22 and mix it with distilled water, adjust the pH value to 7.9-8.4 with NaOH, stir at 200-300 rpm for 30-40 min to obtain a carboxylated graphene suspension, add the imidazole quaternary ammonium salt obtained in step S21, stir again for 30 min, ultrasonicate for 2 h, filter by suction, wash the filter cake with distilled water, and dry at 80-100° C. to obtain modified graphene;

[0014] S3: Add modified carbon nanotubes and modified graphene to anhydrous ethanol and mix well, stir at 400-500 rpm for 20-30 min, add n-propylamine and stir for 10-20 min, then add metal ion ethanol solution dropwise at a rate of 1-2 mL / min while stirring, continue stirring for 40-60 min after the addition is completed, filter, wash the filter cake with deionized water, and vacuum dry at 25°C and a vacuum degree of -0.09~-0.05MPa to obtain a composite material of graphene-modified carbon nanotubes.

[0015] Further, in step S11, the HNO 3 Aqueous solution with H 2 O 2 The volume ratio of the aqueous solution is 2.5-3.5:1.

[0016] Furthermore, in step S11, the carbon nanotubes and HNO 3 / H 2 O 2 The dosage ratio of the mixed solution is 1-1.5 g:100 mL.

[0017] Furthermore, in step S12, the ratio of carboxyl carbon nanotubes to thionyl chloride is 1 g: 15-20 mL.

[0018] Furthermore, in step S13, the mass ratio of the chlorinated carbon nanotubes to the 2-(4-aminophenyl)butyric acid is 1:1-1.5.

[0019] Furthermore, in step S13, the usage ratio of the acyl chloride carbon nanotubes to pyridine is 1 g:0.1-0.15 mL.

[0020] Furthermore, in step S13, the volume ratio of pyridine to DMF is 1:400.

[0021] Furthermore, in step S21, the ratio of the amount of benzimidazole to dimethyl sulfoxide is 0.1-0.2 g:5 mL.

[0022] Furthermore, in step S21, the mass ratio of the benzimidazole to 2,3-epoxypropyltrimethylammonium chloride is 1:1.2-1.6.

[0023] Furthermore, in step S21, the volume ratio of acetone to dimethyl sulfoxide is 4-6:1.

[0024] Furthermore, in step S22, the mass concentration of the graphene oxide dispersed in deionized water is 0.04-0.08 g / mL.

[0025] Furthermore, in step S22, the mass ratio of the chloroacetic acid to the graphene oxide is 1:2-4.

[0026] Furthermore, in step S22, the mass ratio of NaOH to chloroacetic acid is 6:3-5.

[0027] Furthermore, in step S23, the mass concentration of carboxylated graphene in distilled water is 4-6 mg / mL.

[0028] Furthermore, in step S23, the mass ratio of the imidazole quaternary ammonium salt to the carboxylated graphene is 2-2.5:1.

[0029] Furthermore, in step S3, the mass ratio of the modified carbon nanotubes to the modified graphene is 1:2.2-4.

[0030] Furthermore, in step S3, the mass concentration of the modified carbon nanotubes in anhydrous ethanol is 10-18 mg / mL.

[0031] Furthermore, in step S3, the mass ratio of n-propylamine to modified carbon nanotubes is 1:6-8.

[0032] Furthermore, in step S3, the concentration of metal ions in the metal ion ethanol solution is 6-10 mol / L.

[0033] Further, in step S3, the metal ion is Fe 3+ 、Ni 2+ 、Ag + , Pt 4+ , Pd 2+ At least one of .

[0034] Furthermore, in step S3, the ratio of the metal ions to the modified carbon nanotubes is 1 mol: 15-20 g.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] The present invention compounds graphene and carbon nanotubes to prepare modified carbon nanotubes, which are cross-linked with graphene and metal ions to improve electrical properties. In the carbon nanotube modification process of the present invention, the carbon nanotubes are first carboxylated, then the carboxyl groups are chlorinated, and then reacted with 2-(4-aminophenyl)butyric acid, and the carbon nanotubes and 2-(4-aminophenyl)butyric acid are connected through amide bonds to complete the surface modification of the carbon nanotubes. The 2-(4-aminophenyl)butyric acid contains a benzene ring and a butyric acid group, has a large steric hindrance effect, significantly improves the dispersibility of the carbon nanotubes, is not easy to agglomerate, and makes the carbon nanotubes easier to insert into the graphene interlayer and evenly dispersed, so that the graphene The layers are separated from each other to avoid graphene agglomeration and stacking, improve the utilization rate of specific surface area, increase specific capacitance, solve the overlapping problem of graphene due to π-π bond conjugation, and improve conductivity. Carbon nanotubes have high dispersion in graphene, and carbon nanotubes can produce a synergistic effect with graphene to improve conductivity efficiency. The large specific surface area of ​​graphene and the high aspect ratio of carbon nanotubes can construct an efficient conductive network, achieve effective contact with electrode active materials, improve their electronic conductivity, and achieve large current rapid charging and discharging performance. The present invention activates and modifies graphene oxide, converting the hydroxyl and epoxy groups on the surface of graphene oxide into carboxyl groups, which is beneficial for subsequent processing; benzimidazole and 2,3-epoxypropyltrimethylammonium chloride are synthesized to form an imidazole quaternary ammonium salt containing an imidazole group and a quaternary ammonium salt cationic group, which has the positive charge of the quaternary ammonium salt. The carboxyl group grafted with graphene is easily ionized under alkaline water conditions, making the surface of the structural layer of graphene oxide negatively charged, and the aminoimidazole quaternary ammonium salt can be inserted into the interlayer of graphene oxide through ionic bond forces, thereby increasing its interlayer spacing, increasing dispersibility, reducing agglomeration, and facilitating the subsequent cross-linking and insertion of carbon nanotubes to improve electrical properties. The present invention also introduces metal ions into the composite material to improve electrical conductivity and mechanical properties, enhance thermal stability, and bond the carboxyl group of 2-(4-aminophenyl)butyric acid, the amino group of n-propylamine and the metal ion on the surface of the modified carbon nanotube through ionic bonds and coordination bonds, -COO - and -NH 3 + Because of the attraction between positive and negative charges, electrostatic attraction is generated, -COO - There is a lone pair of electrons on the carbonyl oxygen in the -NH 3 +The N atoms in the graphene also have lone pairs of electrons, which can also provide lone pairs of electrons to form coordination bonds with metal ions, thereby forming a stable triangular bonding form, forming a cross-linked network structure, not easy to migrate and agglomerate, improving dispersibility, and improving mechanical properties. In addition, the imidazole quaternary ammonium salt can form a complex with the metal ions through the N atoms. The composite material prepared by the present invention presents a surface line network structure, the nanotubes are uniformly dispersed between the graphene sheets, has a large effective specific surface area, is conducive to the transmission of charges, and has excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0038] Figure 1 The conductivity of the composite materials described in Examples 1-3 and Comparative Examples 1-2 of the present invention;

[0039] Figure 2 The cycle performance of the composite materials described in Examples 1-3 and Comparative Examples 1-2 of the present invention;

[0040] Figure 3 The stability of the composite materials described in Examples 1-3 and Comparative Examples 1-2 of the present invention. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments. It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention are purchased through commercial channels.

[0042] Embodiment 1: A method for preparing a composite material of graphene-modified carbon nanotubes, comprising the following steps:

[0043] S1: Preparation of modified carbon nanotubes:

[0044] S11: Preparation of 65wt% HNO 3 aqueous solution and 45wt% H 2 O 2 aqueous solution, HNO 3 175 mL of aqueous solution and H 2 O 2 Mix 50 mL of aqueous solution to obtain HNO 3 / H 2 O 2Mix the solution and add 3 g of carbon nanotubes to HNO 3 / H 2 O 2 The mixed solution (200 mL) was stirred at 300 rpm for 30 min, ultrasonicated at 50 kHz for 30 min, heated under reflux at 120 °C for 2 h, filtered, the filter cake was washed with deionized water, and vacuum dried at 80 °C for 12 h to obtain carboxyl carbon nanotubes.

[0045] S12: Take 2 g of the carboxyl carbon nanotubes obtained in step S11, add 40 mL of thionyl chloride, perform ultrasonic treatment at 40 kHz for 30 min, stir at 80°C and 300 rpm for 28 h, cool to room temperature, filter, wash with DMF and tetrahydrofuran, and vacuum dry at 100°C to obtain acyl chloride carbon nanotubes;

[0046] S13: 2 g of the acyl chloride carbon nanotubes obtained in step S12 were fully mixed with 3 g of 2-(4-aminophenyl)butyric acid, 0.3 mL of pyridine, and 120 mL of DMF, and ultrasonicated at 40 kHz for 30 min, and nitrogen was passed through for 25 min, and then stirred and refluxed at 130°C and 600 rpm for 48 h, and vacuum filtered. The filter cake was washed with DMF and acetone, and dried at 80°C to obtain modified carbon nanotubes;

[0047] S2: Preparation of modified graphene:

[0048] S21: Take 20 g of benzimidazole and add 500 mL of dimethyl sulfoxide. Stir at 90°C and 200 rpm for 20 min, add 32 g of 2,3-epoxypropyltrimethylammonium chloride, continue stirring and reacting at 90°C for 24 h, pour into 3 L of acetone for precipitation, filter, wash with deionized water, and dry under vacuum at room temperature for 48 h to obtain imidazole quaternary ammonium salt;

[0049] S22: 10 g of graphene oxide was dispersed in 125 mL of deionized water, ultrasonicated at 600 W for 30 min, 3 g of NaOH and 2.5 g of chloroacetic acid were added, ultrasonicated for 3 h, centrifuged at 8000 rpm for 25 min, and vacuum dried at 70 °C to obtain carboxylated graphene;

[0050] S23: Take 3 g of the carboxylated graphene obtained in step S22 and mix it with 500 mL of distilled water, adjust the pH value to 8.4 with NaOH, stir at 300 rpm for 40 min to obtain a carboxylated graphene suspension, add 7.5 g of the imidazole quaternary ammonium salt obtained in step S21, stir again for 30 min, ultrasonicate for 2 h, filter by suction, wash the filter cake with distilled water, and dry at 100°C to obtain modified graphene;

[0051] S3: Add 0.54 g of modified carbon nanotubes and 2.16 g of modified graphene to 30 mL of anhydrous ethanol and mix well. Stir at 500 rpm for 30 min, add 67.5 mg of n-propylamine and stir for 20 min, then add 2.7 mL of 10 mol / L ferric chloride ethanol solution dropwise at a rate of 2 mL / min while stirring. After the addition is completed, continue stirring for 60 min, filter, wash the filter cake with deionized water, and vacuum dry at 25°C and a vacuum degree of -0.05 MPa to obtain a composite material of graphene-modified carbon nanotubes.

[0052] Embodiment 2: A method for preparing a composite material of graphene-modified carbon nanotubes, comprising the following steps:

[0053] S1: Preparation of modified carbon nanotubes:

[0054] S11: Preparation of 65wt% HNO 3 aqueous solution and 45wt% H 2 O 2 aqueous solution, HNO 3 125 mL of aqueous solution and H 2 O 2 Mix 50 mL of aqueous solution to obtain HNO 3 / H 2 O 2 Mix the solution and add 2 g of carbon nanotubes to HNO 3 / H 2 O 2 The mixed solution (200 mL) was stirred at 200 rpm for 30 min, ultrasonicated at 40 kHz for 30 min, heated under reflux at 120 °C for 2 h, filtered, the filter cake was washed with deionized water, and vacuum dried at 80 °C for 12 h to obtain carboxyl carbon nanotubes.

[0055] S12: Take 2 g of the carboxyl carbon nanotubes obtained in step S11, add 30 mL of thionyl chloride, perform ultrasonic treatment at 40 kHz for 20 min, stir at 60°C and 200 rpm for 24 h, cool to room temperature, filter, wash with DMF and tetrahydrofuran, and vacuum dry at 80°C to obtain acyl chloride carbon nanotubes;

[0056] S13: 2 g of the acyl chloride carbon nanotubes obtained in step S12 was fully mixed with 2 g of 2-(4-aminophenyl)butyric acid, 0.2 mL of pyridine, and 80 mL of DMF, and ultrasonicated at 40 kHz for 20 min, and then refluxed with stirring at 110° C. and 500 rpm for 44 h, and vacuum filtered. The filter cake was washed with DMF and acetone, and dried at 80° C. to obtain modified carbon nanotubes;

[0057] S2: Preparation of modified graphene:

[0058] S21: Take 10 g of benzimidazole and add 500 mL of dimethyl sulfoxide, stir at 80°C and 150 rpm for 20 min, add 12 g of 2,3-epoxypropyltrimethylammonium chloride, continue stirring and reacting at 80°C for 22 h, pour into 2 L of acetone for precipitation, filter, wash with deionized water, and dry in vacuum at room temperature for 48 h to obtain imidazole quaternary ammonium salt;

[0059] S22: 10 g of graphene oxide was dispersed in 250 mL of deionized water, ultrasonicated at 600 W for 20 min, 10 g of NaOH and 5 g of chloroacetic acid were added, ultrasonicated for 2 h, centrifuged at 8000 rpm for 15 min, and dried in vacuum at 60 °C to obtain carboxylated graphene;

[0060] S23: Take 2 g of the carboxylated graphene obtained in step S22 and mix it with 500 mL of distilled water, adjust the pH value to 7.9 with NaOH, stir at 200 rpm for 30 min to obtain a carboxylated graphene suspension, add 4 g of the imidazole quaternary ammonium salt obtained in step S21, stir again for 30 min, ultrasonicate for 2 h, filter by suction, wash the filter cake with distilled water, and dry at 80°C to obtain modified graphene;

[0061] S3: Add 0.9 g of modified carbon nanotubes and 1.98 g of modified graphene to 90 mL of anhydrous ethanol and mix well. Stir at 400 rpm for 20 min, add 0.15 g of n-propylamine and stir for 10 min, then add 10 mL of 6 mol / L nickel nitrate ethanol solution dropwise at a rate of 1 mL / min while stirring. After the addition is complete, continue stirring for 40 min, filter, wash the filter cake with deionized water, and vacuum dry at 25°C and a vacuum degree of -0.09 MPa to obtain a composite material of graphene-modified carbon nanotubes.

[0062] Embodiment 3: A method for preparing a composite material of graphene-modified carbon nanotubes, comprising the following steps:

[0063] S1: Preparation of modified carbon nanotubes:

[0064] S11: Preparation of 65wt% HNO 3 aqueous solution and 45wt% H 2 O 2 aqueous solution, HNO 3 150 mL of aqueous solution and H 2 O 2 Mix 50 mL of aqueous solution to obtain HNO 3 / H 2 O 2 Mix the solution and add 2.5 g of carbon nanotubes to HNO 3 / H 2 O2 The mixed solution was stirred at 250 rpm for 30 min, ultrasonicated at 45 kHz for 30 min, heated under reflux at 120 °C for 2 h, filtered, the filter cake was washed with deionized water, and vacuum dried at 80 °C for 12 h to obtain carboxyl carbon nanotubes.

[0065] S12: Take 2 g of the carboxyl carbon nanotubes obtained in step S11, add 35 mL of thionyl chloride, perform ultrasonic treatment at 40 kHz for 25 min, stir at 70°C and 250 rpm for 26 h, cool to room temperature, filter, wash with DMF and tetrahydrofuran, and vacuum dry at 90°C to obtain acyl chloride carbon nanotubes;

[0066] S13: 2 g of the acyl chloride carbon nanotubes obtained in step S12 was fully mixed with 2.5 g of 2-(4-aminophenyl)butyric acid, 0.25 mL of pyridine, and 100 mL of DMF, and ultrasonicated at 40 kHz for 25 min, and then purged with nitrogen for 22 min. The mixture was stirred and refluxed at 120° C. and 550 rpm for 46 h, and vacuum filtered. The filter cake was washed with DMF and acetone, and dried at 80° C. to obtain modified carbon nanotubes.

[0067] S2: Preparation of modified graphene:

[0068] S21: Take 15 g of benzimidazole and add 500 mL of dimethyl sulfoxide, stir at 85°C and 180 rpm for 20 min, add 2,3-epoxypropyltrimethylammonium chloride 21 g, continue stirring and reacting at 85°C for 23 h, pour into 2.5 L of acetone for precipitation, filter, wash with deionized water, and dry in vacuum at room temperature for 48 h to obtain imidazole quaternary ammonium salt;

[0069] S22: 6 g of graphene oxide was dispersed in 100 mL of deionized water, ultrasonicated at 600 W for 25 min, 3 g of NaOH and 2 g of chloroacetic acid were added, ultrasonicated for 2.5 h, centrifuged at 8000 rpm for 20 min, and vacuum dried at 65 °C to obtain carboxylated graphene;

[0070] S23: Take 2.5 g of the carboxylated graphene obtained in step S22 and mix it with 500 mL of distilled water, adjust the pH value to 8.1 with NaOH, stir at 250 rpm for 35 min to obtain a carboxylated graphene suspension, add 6 g of the imidazole quaternary ammonium salt obtained in step S21, stir again for 30 min, ultrasonicate for 2 h, filter by suction, wash the filter cake with distilled water, and dry at 90° C. to obtain modified graphene;

[0071] S3: Add 0.8 g of modified carbon nanotubes and 2.4 g of modified graphene to 50 mL of anhydrous ethanol and mix well. Stir at 450 rpm for 25 min, add 0.12 g of n-propylamine and stir for 15 min, then add 6.25 mL of 8 mol / L chloroplatinic acid ethanol solution dropwise at a rate of 1.5 mL / min while stirring. After the addition is completed, continue stirring for 50 min, filter, wash the filter cake with deionized water, and vacuum dry at 25°C and a vacuum degree of -0.07 to obtain a composite material of graphene-modified carbon nanotubes.

[0072] The only difference between Comparative Example 1 and Example 1 is that carbon nanotubes are used instead of modified carbon nanotubes.

[0073] The only difference between Comparative Example 2 and Example 1 is that graphene oxide is used instead of modified graphene.

[0074] The only difference between Comparative Example 3 and Example 1 is that no metal ion ethanol solution is added.

[0075] The only difference between Comparative Example 4 and Example 11 is that n-propylamine is not added.

[0076] Experimental Example 1: Active material Li 4 Ti 5 O 12 The composite materials obtained in Example 1 and Comparative Examples 1-4 and the binder LA132 were mixed in a weight ratio of 90:5:5, ground evenly in an agate mortar, evenly coated on an aluminum foil, and dried in a vacuum oven at 80°C for 12 h to prepare an electrode sheet, wherein the active material loading was 5 mg / cm 2 . A button cell was assembled using a CR2032 button cell model, with a metal lithium sheet as the counter electrode, a Celgard 2400 separator, and an electrolyte of 1 mol / L LiPF6 / EC:DEC:DMC (1:1:1 volume ratio). The rate performance was tested by constant current charge and discharge at room temperature. The test voltage range was 3.0V-1.0V, and the test current size was expressed as 0.2 C, 1.0 C, 3.0 C, and 5.0 C in terms of rate. The results are shown in Table 1.

[0077] Table 1:

[0078]

[0079] The results in Table 1 show that the discharge specific capacity of Example 1 is higher, and the specific capacities of Comparative Examples 1-4 are lower than that of Example 1. The carbon nanotubes in Comparative Example 1 are not modified, so that the carbon nanotubes have poor dispersibility and are easier to agglomerate, and the degree of crosslinking with modified graphene and metal ions is reduced, and the dispersibility between graphene sheets is poor. The graphene in Comparative Example 2 is not modified, so that the spacing between graphene sheets is reduced, the dispersibility is reduced, and the effective specific surface area is reduced. Comparative Examples 3 and 4 do not add metal ions and n-propylamine, respectively, and cannot form a triangular bonding structure, and the dispersibility is reduced.

[0080] Experimental Example 2: The composite materials of Examples 1-3 and Comparative Examples 1-4, ethanol and water were mixed uniformly in a mass ratio of 1:1:9, ground, coated with a 50 μm thickness using an automatic coating machine, dried, and the conductivity of the composite materials of Examples 1-3 and Comparative Examples 1-4 was tested using a four-probe tester. The test results are shown in Figure 1 .

[0081] Figure 1 The results show that the conductivity of Examples 1-3 is above 1000 S / cm, and the conductivity of Examples 1-3 is better than that of Comparative Examples 1-4. The carbon nanotubes of Comparative Example 1 are not modified and are easy to agglomerate, which affects the conductivity. The graphene of Comparative Example 2 is not modified, and the graphene is easy to stack and agglomerate, which affects the dispersed intercalation of the carbon nanotubes and reduces the conductivity. No metal ions are added in Comparative Example 3, and the conductivity decreases. No n-propylamine is added in Comparative Example 4, and the metal ions are easy to agglomerate, and the conductivity decreases.

[0082] Experimental Example 3: The prepared button cell was tested using a blue electric tester with a voltage range of 3V-4.4V, 0.1C charge and discharge for one cycle, then charged at 0.5C constant current and constant voltage, with a cut-off current of 0.05C, and discharged at 1C current for constant current. The capacity retention rate was tested at 10, 20, 40, 60, 80 and 100 cycles. The results are as follows: Figure 2 shown.

[0083] Figure 2 The results show that after 100 cycles, the capacity retention rate of Example 1 is 89.49%, and the capacity retention rate of Comparative Examples 1-4 is 75.91%-84.79%. The cycle performance of Example 1 is significantly better than that of Comparative Examples 1-4. The modification of graphene and carbon nanotubes and the introduction of metal ions improve the electronic conductivity of the material, increase the transport and diffusion rate of charged ions, and improve the cycle performance.

[0084] Experimental Example 4: The graphene nanocomposites prepared in Example 1 and Comparative Examples 1-4 were placed in a TGA device, and the temperature was raised to 200°C, 300°C and 500°C at a rate of 10°C / min under a nitrogen atmosphere. The mass loss percentage was tested at 200°C, 300°C and 500°C, and the results were recorded as follows: Figure 3 shown.

[0085] Depend on Figure 3 As can be seen from the results, the composite material prepared by the present invention has good thermal stability and can have a higher residual amount at high temperature; from the results of Comparative Example 1 and Example 1, it can be seen that the unmodified carbon nanotubes have decreased dispersibility, poor uniformity, and decreased degree of crosslinking with graphene and metal ions, affecting the thermal stability; from the results of Comparative Example 2 and Example 1, it can be seen that the interlayer spacing of the unmodified graphene sheets is small, which is not conducive to the intercalation of carbon nanotubes, the degree of crosslinking is poor, the metal ion loading amount decreases, and the thermal stability is poor; Comparative Example 3 does not add metal ions, and the thermal stability decreases; Comparative Example 4 does not add n-propylamine, and the metal ions are easy to agglomerate, affecting the thermal stability.

[0086] Experimental Example 5: 10 g of the modified carbon nanotubes and carboxyl carbon nanotubes prepared in Examples 1-3 were dispersed in 100 mL of 50 vol% ethanol aqueous solution. After standing for 30 days, the precipitate was aspirated, dried, and weighed. The percentage of the precipitate to the total weight of the carbon nanotubes was calculated. The results are shown in Table 2.

[0087] Table 2:

[0088]

[0089] The results in Table 1 show that after the modified carbon nanotubes prepared in Examples 1-3 were placed for 30 days, the precipitation ratio did not exceed 2.5%, while the precipitation ratio of the carboxyl carbon nanotubes was relatively high, at 10.9%, significantly higher than that of Examples 1-3, indicating that the modified carbon nanotubes in Examples 1-3 have excellent dispersibility and stability.

[0090] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A method for preparing a composite material of graphene-modified carbon nanotubes, characterized in that: The following steps are involved: S1: Preparation of modified carbon nanotubes: S11: preparing an HNO3 aqueous solution and an H2O2 aqueous solution, mixing them to obtain an HNO3 / H2O2 mixed solution, adding carbon nanotubes to the HNO3 / H2O2 mixed solution, stirring, ultrasonicating, heating under reflux, filtering, washing the filter cake with deionized water, and vacuum drying to obtain carboxyl carbon nanotubes; S12: adding thionyl chloride to the carboxyl carbon nanotubes obtained in step S11, performing ultrasonication, stirring for reaction, cooling, filtering, washing, and vacuum drying to obtain acyl chloride carbon nanotubes; S13: the acyl chloride carbon nanotubes obtained in step S12 are fully mixed with 2-(4-aminophenyl)butyric acid, pyridine and DMF, subjected to ultrasonication, nitrogen flow, stirred and refluxed, filtered, the filter cake is washed and dried to obtain modified carbon nanotubes; S2: Preparation of modified graphene: S21: Add dimethyl sulfoxide to benzimidazole, stir, add 2,3-epoxypropyltrimethylammonium chloride, continue to stir and react, pour into acetone for precipitation, filter, wash, and dry to obtain imidazole quaternary ammonium salt; S22: dispersing graphene oxide in deionized water, ultrasonicating, adding NaOH and chloroacetic acid, continuing ultrasonicating, centrifuging, and vacuum drying to obtain carboxylated graphene; S23: taking the carboxylated graphene obtained in step S22 and mixing it with distilled water, adjusting the pH value, stirring to obtain a carboxylated graphene suspension, adding the imidazole quaternary ammonium salt obtained in step S21, stirring again, ultrasonicating, filtering, washing the filter cake with distilled water, and drying to obtain modified graphene; S3: adding modified carbon nanotubes and modified graphene to anhydrous ethanol, mixing and stirring, adding n-propylamine and stirring, then dropping metal ion ethanol solution while stirring, continuing to stir after the dropping is completed, filtering, washing the filter cake, and vacuum drying to obtain a composite material of graphene-modified carbon nanotubes.

2. The method for preparing the composite material of graphene-modified carbon nanotubes according to claim 1, characterized in that: In step S11, the volume ratio of the HNO3 aqueous solution to the H2O2 aqueous solution is 2.5-3.5:1; the amount ratio of the carbon nanotubes to the HNO3 / H2O2 mixed solution is 1-1.5 g:100 mL.

3. The method for preparing the composite material of graphene-modified carbon nanotubes according to claim 2, characterized in that: In step S12, the ratio of carboxyl carbon nanotubes to thionyl chloride is 1 g: 15-20 mL.

4. The method for preparing the composite material of graphene-modified carbon nanotubes according to claim 3, characterized in that: In step S13, the mass ratio of acyl chloride carbon nanotubes to 2-(4-aminophenyl)butyric acid is 1:1-1.5; the amount ratio of acyl chloride carbon nanotubes to pyridine is 1 g:0.1-0.15 mL; and the volume ratio of pyridine to DMF is 1:

400.

5. The method for preparing the composite material of graphene-modified carbon nanotubes according to claim 4, characterized in that: In step S21, the dosage ratio of benzimidazole to dimethyl sulfoxide is 0.1-0.2 g:5 mL; the mass ratio of benzimidazole to 2,3-epoxypropyltrimethylammonium chloride is 1:1.2-1.6; and the volume ratio of acetone to dimethyl sulfoxide is 4-6:

1.

6. The method for preparing the composite material of graphene-modified carbon nanotubes according to claim 5, characterized in that: In step S22, the mass concentration of the graphene oxide dispersed in deionized water is 0.04-0.08 g / mL; the mass ratio of chloroacetic acid to graphene oxide is 1:2-4; and the mass ratio of NaOH to chloroacetic acid is 6:3-5.

7. The method for preparing the composite material of graphene-modified carbon nanotubes according to claim 6, characterized in that: In step S23, the mass concentration of carboxylated graphene in distilled water is 4-6 mg / mL; and the mass ratio of imidazole quaternary ammonium salt to carboxylated graphene is 2-2.5:

1.

8. The method for preparing the composite material of graphene-modified carbon nanotubes according to claim 7, characterized in that: In step S3, the mass ratio of modified carbon nanotubes to modified graphene is 1:2.2-4; the mass concentration of modified carbon nanotubes in anhydrous ethanol is 10-18 mg / mL; the mass ratio of n-propylamine to modified carbon nanotubes is 1:6-8; the concentration of metal ions in the metal ion ethanol solution is 6-10 mol / L; the metal ion is Fe 3+ 、Ni 2+ 、Ag + , Pt 4+ , Pd 2+ At least one of the following: the ratio of metal ions to modified carbon nanotubes is 1 mol: 15-20 g.

Citation Information

Patent Citations

  • A method for preparing graphene / carbon nanotube composite materials and their applications

    CN106861617B

  • Graphene / carbon nanotube composite material, preparation method and application thereof

    CN109994733A

  • Preparation method of graphene-carbon nanotube compound film based on three-dimensional network appearance

    CN102417176A

  • Preparation method of graphene / carbon nano tube disperse system high-polymer based composite material

    CN102807737A